Botaniki, njihovo delo in herbarijske zbirke praprotnic in semenk v Prirodoslovnem muzeju Slovenije - Praprotnik, Nada (Scopolia, 2015)
The introductory part of the paper summarizes a short history of botanical research in Slovenia. The chapter dealing with herbaria in the Slovenian Museum of Natural History describes the main collections of vascular plants, their history and problems encountered in this respect by the Museum's custodians from Angela Piskernik and Tone Wraber to Nada Praprotnik. Herbarium collections and their authors are presented in chronological order. The overview starts with the oldest known collection in Slovenia, i.e. Flysser's herbarium (1696), proceeds with nature historians and collections in the second part of the 18th century and in the ensuing century, and ends with the first half of the 20th century with the prominent collection Flora exsiccata Carniolica by Alfonz Paulin, and the botanist and museum worker Angela Piskernik. The taxa in the Museum's collections, which have their typical localities in Slovenia and were, furthermore, new for the Slovenian flora and named after natural historians or in any way associated with their work, are dealt with in greater detail. In the end, an extensive review of sources and references is given.
Keywords: botaniki; botanists; herbarijske zbirke; herbarium collections; history; Ljubljana; praprotnice; Prirodoslovni muzej Slovenije; semenke; Slovenia; Slovenian Museum of Natural History; Slovenija; vascular plants; zgodovina botanike